Prader-Willi Syndrome: Genetics, Phenotype, and Management - Constantine Samaan, M. (Current Psychiatry Reviews, 2014)
Prader-Willi syndrome (PWS) is an imprinting neurodevelopmental disorder resulting from loss of function of paternal PWS critical genomic region on chromosome 15q11-q13. The clinical course in PWS is characterized by neonatal hypotonia with feeding difficulties and failure to thrive. This is followed by onset of hyperphagia leading to obesity. Patients with PWS have several neurobehavioral and psychiatric features including learning disability, autism spectrum disorder, temper tantrums, repetitive behaviors, skin picking, affective disorders and psychosis. In this review, we focus on genotype–phenotype correlations in PWS. We also describe the current protocol for genetic testing to establish the diagnosis, the differential diagnosis of PWS, and the neurobehavioral and psychiatric manifestations and their management.
Keywords: obesity